Options for Increasing Mongolia’s Livestock Sector Exports - A Revealed Comparative Advantage Analysis - Tumur, Erdenechuluun; Heijman, Wim; Gurjav, Enkh-Amgalan; Agipar, Bakey; Heerink, Nico (Mongolian Journal of Agricultural Sciences, 2020)
Mongolia is a country with rich natural resources, including more than 70 million domesticated animals. The livestock sector is the traditional economic sector of Mongolia, and it is a major food source of the nation. Currently, the country faces an overgrazing problem caused by an increase in the number of animals whereas rangeland carrying capacity is limited. Exporting more meat and other products of animal origin has the potential to reduce the livestock population to sustainable levels, reduce overgrazing pressure, and increase the country’s export income. Policies aimed at promoting animal product exports should take the comparative advantages of different types of products of animal origin into account in order to maximize their impact. This paper aims to provide science-based evidence to support such policies by investigating the comparative advantage of meat and other selected products of animal-origin using the revealed comparative advantage index. Official statistics for 81 products over nine years were used for the data analysis. The results suggest that Mongolia’s meat export policy should focus on large volumes and relatively lower processing level products in the short run and should shift to differentiated value-added products in the long run. We recommend that the Government of Mongolia improves its meat sector’s regulation and develops formal supply chains in order to effectively monitor food safety and create high-quality Mongolian brand products of animal origin.